Digitalisasi Sekolah Sebagai Pendorong Pembelajaran Efektif dan Kreatif di SMA Negeri 1 Semarang - Eko Pujiono; Munirotun Munirotun; Titik Haryati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Digitalization in education is a pressing issue in Indonesia, especially in the context of the rapid technological advancements driven by the 4.0 industrial revolution. This research focuses on the impact of digitalization on learning effectiveness and student creativity at SMA Negeri 1 Semarang. The primary objective is to assess how digital tools such as Learning Management Systems (LMS) influence the quality of teaching and foster creativity among students. Using a qualitative descriptive approach, data were collected through interviews, observations, and document studies. The findings indicate that the implementation of LMS at SMA Negeri 1 Semarang has positively affected learning by offering more flexible access to learning materials and enhancing student engagement. However, challenges related to teacher training and unequal access to technology for students remain significant barriers. The research suggests that for digitalization to be fully effective, continuous professional development for educators and equal access to digital devices for students are essential. The implications of this study emphasize the need for supportive policies and infrastructures to optimize the benefits of digital education.